2013
DOI: 10.1038/ejhg.2013.116
|View full text |Cite
|
Sign up to set email alerts
|

The sex-specific associations of the aromatase gene with Alzheimer’s disease and its interaction with IL10 in the Epistasis Project

Abstract: Epistasis between interleukin-10 (IL10) and aromatase gene polymorphisms has previously been reported to modify the risk of Alzheimer's disease (AD). However, although the main effects of aromatase variants suggest a sex-specific effect in AD, there has been insufficient power to detect sex-specific epistasis between these genes to date. Here we used the cohort of 1757 AD patients and 6294 controls in the Epistasis Project. We replicated the previously reported main effects of aromatase polymorphisms in AD ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 76 publications
(111 reference statements)
2
33
0
1
Order By: Relevance
“…The importance of aromatase as a neuroprotective molecule in humans is suggested by the existence of genetic variants of the enzyme that confer an increased risk for Alzheimer's disease [25][26][27][28] . These genetic variants of aromatase may result in decreased oestradiol synthesis in the brain, which, together with decreased serum oestradiol levels in postmenopausal women or serum testosterone levels in aged men, may increase the risk for developing neurodegenerative diseases.…”
Section: Lipid Raftsmentioning
confidence: 99%
“…The importance of aromatase as a neuroprotective molecule in humans is suggested by the existence of genetic variants of the enzyme that confer an increased risk for Alzheimer's disease [25][26][27][28] . These genetic variants of aromatase may result in decreased oestradiol synthesis in the brain, which, together with decreased serum oestradiol levels in postmenopausal women or serum testosterone levels in aged men, may increase the risk for developing neurodegenerative diseases.…”
Section: Lipid Raftsmentioning
confidence: 99%
“…These data query the relationship between the IL-10 -1082 genetic polymorphism and AD risk and strongly imply differences between ethnic groups. Moreover, in a recent investigation by Medway et al, association of the IL-10 -1082 genetic polymorphism with AD was only found in women [120], suggesting a sex-specific effect of this SNP. It has been reported that this SNP alters IL-10 gene transcription and plasma IL-10 concentrations [119,121], which may account for the functional activity.…”
Section: Il-10mentioning
confidence: 99%
“…Aromatase expression and activity is necessary for proper neurobehavioral development in males and females. Only a few studies have examined men and women separately and they reported an association exclusively in women (Butler et al, 2010;Corbo et al, 2009;Medway et al, 2014). In contrast with depression, a number of studies have examined the associations between several CYP19A1 variants and cognitive impairment or Alzheimer's disease Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%